Particular Councils and Synodality - Maria d’Arienzo (Religions)
This paper underlines the importance of the Particular Councils in the implementation of the principle of synodality, a central theme in Pope Francis’ pontificate. A recovery of the role previously recognised to Particular Councils can, in fact, contribute to a more balanced participation of the People of God in carrying out the Church’s mission.